Apoptosis, Cell Signaling, and Human Diseases Molecular Mechanisms, Volume 2 - Srivastava, Rakesh (Humana Press : Imprint: Humana, 2007)
Apoptosis, Cell Signaling, and Human Diseases: Molecular Mechanisms, Volumes 1 & 2, present a concise synthesis of recent developments in the understanding of both cell survival and apoptotic pathways. Particular attention is given to apoptosis in human diseases, such as different forms of cancer and neurodegenerative diseases. These comprehensive volumes integrate the most innovative and current findings from several related disciplines of scientific research, including pathology, genetics, virology, cell biology, immunology, and molecular biology. Volume 1 is divided into two sections: "Malignant Transformation and Metastasis" and "Molecular Basis of Disease Therapy." Volume 2 follows a similar structure and is divided into sections entitled "Kinases and Phosphate" and "Molecular Basis of Cell Death." All of the contributors are at the forefront of scientific discovery, and the reviews they present systemically examine the most exciting and innovative aspects of their particular areas of expertise. Researchers will find these volumes of major benefit as they search for novel and more effective treatments for human diseases.